Genotypic Diversity and Short-term Response to Shading Stress in a Threatened Seagrass: Does Low Diversity Mean Low Resilience? - Evans, Suzanna M.; Vergés, Adriana; Poore, Alistair G. B. (Frontiers in Plant Science, 2017)
Seagrasses that are predominantly clonal often have low levels of genetic variation within populations and predicting their response to changing conditions requires an understanding of whether genetic variation confers increased resistance to environmental stressors. A higher level of genetic diversity is assumed to benefit threatened species due to the increased likelihood of those populations having genotypes that can persist under environmental change. To test this idea, we conducted an in situ shading experiment with six geographically distinct meadows of the threatened seagrass Posidonia australis that vary in genetic diversity. Different genotypes within meadows varied widely in their physiological and growth responses to reduced light during a simulated short-term turbidity event. The majority of meadows were resistant to the sudden reduction in light availability, but a small subset of meadows with low genotypic diversity were particularly vulnerable to the early effects of shading, showing substantially reduced growth rates after only three weeks. Using the photosynthetic performance (maximum quantum yield) of known genotypes, we simulated meadows of varying genetic diversity to show that higher diversity can increase meadow resilience to stress by ensuring a high probability of including a high-performing genotype. These results support the hypothesis that complementarity among genotypes enhances the adaptive capacity of a population, and have significant implications for the conservation of declining P. australis meadows close to the species range edge on the east coast of Australia, where the genotypic diversity is low.